Smartphone Use in Clinical Practice: Technological Fad or the Future Physician's Assistant? Pametni telefon v klinični praksi: tehnološka modna muha ali zdravnikov bodoči osebni asistent? - Kodela, Aleš; Kodela, Miha; Dinevski, Dejan (Acta Medico-Biotechnica, 2021)
Over the last few years, mobile phones have been undergoing rapid development, especially with the emergence of smartphones. Smartphones have their own operating system that is capable of running many user–installed applications. Their potential for use in the medical field was quickly acknowledged. More than 80% of physicians in the USA own a smartphone, and their use facilitates a rapid treatment, decreases the number of medical errors and allows a quicker access to patient and reference information. However, there is still some room for improvement. There are still some open questions regarding security, privacy and reliability of smartphone use, but their future use in clinical practice seems to be very promising.
Keywords: smartphone; application; medicine; android; healthcare